Tumor redox-responsive minimalist B/Fe nano-chains for chemodynamically enhanced ferroptosis and synergistic boron neutron capture therapy - Wang, Mixue (2024)
Boron neutron capture therapy (BNCT) as a binary targeted particle radiotherapy strategy has shown potent anti-cancer potential. However, biological barriers and restricted blood supply pose challenges in achieving adequate boron concentration within deep-seated tumor lesions. BNCT with other anti-cancer therapies, such as X-ray radiotherapy and photothermal therapy, is devised to address the limitations of BNCT efficiency. However, the potential risk of organ-accumulating toxicity and treatment complexity of dual exogenous activation hinders its development. To address this problem, newly redox-responsive boron nano-chains (RBNC) are reported that combine BNCT and endogenous chemodynamic therapy (CDT)-enhanced ferroptosis. RBNC specifically activates nanoparticle size conversion (large-to-small) in response to GSH/H2O2 in the tumor microenvironment, releasing boron delivery agents boron quantum dots (BQD) and Fe3+. RBNC exhibits negligible systemic toxicity while demonstrating high boron accumulation at tumor. Meanwhile, the introduction of Fe3+ not only produces ·OH through reaction with H2O2, but also depletes GSH and reduces GPX4 activity in tumors, resulting in amplified intracellular oxidative stress and chemodynamically enhanced ferroptosis. Thus, the work provides a strategy to solve the problem of insufficient boron concentration and poor targeting of boron delivery agents and fill the gaps of BNCT combined with CDT and ferroptosis.